Empowering workers’ involvement: Unveiling the dynamics of communication, recognition, productivity, and decision-making in the RMG sector - Hawlader, Md. Rasel; Rana, Md. Masud; Kalam, Abul; Polas, Mohammad Rashed Hasan (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: This study investigates the relationship between workers' perspectives on communication, recognition, productivity, and their involvement in the Readymade Garment (RMG) sector policymaking. Research Methodology:  A survey of 226 individuals from Bangladesh's RMG sector was conducted using a structured questionnaire. Data were analyzed with SPSS V.25, applying chi-square and other statistical methods to test the hypotheses. The study explores the relationship between communication, recognition, productivity, and worker perception. Results: The study finds a significant positive relationship between employees' perceptions of communication, recognition, productivity, and their involvement in decision-making in Bangladesh's RMG sector. Employee participation notably impacts the organization's decision-making process, highlighting the importance of engagement in driving workplace dynamics. Conclusions: The study highlights that employee involvement in decision-making boosts organizational performance, productivity, and commitment. Participatory management is essential, and both formal and informal engagement methods are crucial for success. The findings suggest significant potential for expanding employee involvement, particularly in the RMG industry. Limitations: While many studies examined the workers’ participation in decision-making in the various sectors, only a few studies have focused on the RMG sectors to explore the effects of communication, employee recognition, and productivity on the workers’ participation in decision-making. Contributions: The study reveals that the organization’s total effectiveness is reflected in how deeply workers are involved in decision-making. The degree of involvement is a key determining element since encouraging people to engage instead of just dragging them along is essential for enhancing performance and ensuring commitment.